Aligned CP-violating Higgs sector canceling the electric dipole moment - Shinya Kanemura; Mitsunori Kubota; Kei Yagyu (Journal of High Energy Physics, 2020)
Abstract We discuss the effect of CP violation in the aligned scenario of the general two-Higgs-doublet model, in which the Higgs potential and the Yukawa interaction provide additional CP-violating phases. An alignment is imposed to the Yukawa interaction in order to avoid dangerous flavor changing neutral currents. The Higgs potential is also aligned such that the coupling constants of the lightest Higgs boson, which is identified as the discovered Higgs boson with the mass of 125 GeV, are the same as those of the standard model. In general, CP-violating phases originated by the Yukawa interaction and the Higgs potential are strongly constrained by the current data for the electric dipole moment (EDM). It is found that in our scenario contributions from the two sources of CP violation can be destructive and consequently their total contribution can satisfy the EDM results, even when each CP-violating phase is large. Such a large CP-violating phase can be tested at collider experiments by looking at the angular distributions of particles generated by the decays of the additional Higgs bosons.